Comprender el Convenio sobre pueblos Indigenas y tribales, 1989 (nuþm. 169) : Manual para los mandantes tripartitos de la OIT (Organizacin̤ Internacional del Trabajo, 2013)
This handbook aims to answer some of the essential questions regarding Convention No. 169 and is addressed to governments, employers' and workers' organizations, as well as for Indigenous and tribal peoples.